How to Talk about the Loss of Maternal Love: The Case of Tereza Boučková’s Novel The Year of the Rooster - Filipowicz, Marcin (Bohemistyka, 2023)
The aim of this article is to explore the way in which the literary voice expressing the experience of the loss of maternal love can be constructed. In the Western cultural mainstream, the notion of the sanctity of the mother-child bond strongly prevails, which results in the normative expectation of mothers to identify entirely with the maternal role. Deliberations are based on the analysis of the autobiographical novel Rok kohouta by Czech writer Tereza Boučková. The article tries to answer the question whether providing testimony about such a painful experience is more difficult, or perhaps easier, in the case of adoptive mothers